PPM Pengusaha Kecil Lontong Dengan Menggunakan Sistem TTG di Kelurahan Kupang Krajan di Kecamatan Sawahan Surabaya - siswadi siswadi siswadi; Wahyu Nugroho; Isnaini Muhandhis; Alven Safik Ritonga; Fitrah Hilmi Ghifari (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The Community Empowerment Program (PPM) this time is a rice cake entrepreneur in the Banyu Urip Wetan Gang 10 area, Kupang Krajan Village, Sawahan District, Surabaya. Lontong entrepreneurs in the region formed the Lontong Entrepreneurs Association consisting of 60 groups of lontong entrepreneurs. The workers who make lontong, use a manual system to cook lontong using simple boilers, so the production capacity is relatively low. Every day, each group has to cook an average of 50 kg of rice to be processed into 620 pcs of lontong. Lontong marketing is still limited, lontong is marketed in West Surabaya and surrounding areas. To overcome these problems, we propose solutions, including: (1) designing and manufacturing lontong cooking equipment by applying Appropriate Technology (TTG) to increase rice cake production. (2) marketing management training to provide insight into expanding lontong marketing. The lontong cooking tool that will be designed consists of a large drum for boiling lontong equipped with a thermostat to measure heat. This tool uses Oil Burner fuel. Oil Burner was chosen because the heat is greater and more even, besides that it is also fuel efficient. The innovation of the lontong cooking equipment is expected to make it easier for entrepreneurs to produce rice cakes and increase their productivity. The marketing management training is expected to provide insight to entrepreneurs to expand marketing to other areas. The results of this service activity include: 1) This Lontong cooking machine can speed up the production process with good quality. 2) The existence of this 620 pcs lontong cooking machine equipped with a heat gauge and a sophisticated combustion tool can speed up partners' productivity time to 2 times faster, previously 8 hours of cooking time became only 4 hours. 3) Lontong produced is of higher quality and more perfect, 4) Marketing management training enables partners to add customers, as well as regulate how marketing works.